2011
DOI: 10.1111/j.1365-3113.2011.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of cockroaches (Insecta, Dictyoptera, Blattodea), with placement of aberrant taxa and exploration of out‐group sampling

Abstract: We addressed the phylogeny of cockroaches using DNA sequence data from a broad taxon sample of Dictyoptera and other non‐endopterygotan insect orders. We paid special attention to several taxa in which relationships are controversial, or where no molecular evidence has been used previously: Nocticolidae, a family of small, often cave‐dwelling cockroaches, has been suggested to be the sister group of the predaceous Mantodea or of the cockroach family Polyphagidae; Lamproblatta, traditionally placed in Blattidae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 74 publications
(194 reference statements)
9
84
2
Order By: Relevance
“…These unsurprising results have been suggested several times and concern the monophyly of Blaberidae, (Geoscapheinae + Panesthiinae) and Oxyhaloinae (Maekawa et al 2003;Inward 2007;Pellens et al 2007;Djernaes et al 2012;Legendre et al 2014Legendre et al , 2015. Likewise, a strong support was found, here and in previous studies, for Gyninae, Panchlorinae and Pycnoscelinae.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…These unsurprising results have been suggested several times and concern the monophyly of Blaberidae, (Geoscapheinae + Panesthiinae) and Oxyhaloinae (Maekawa et al 2003;Inward 2007;Pellens et al 2007;Djernaes et al 2012;Legendre et al 2014Legendre et al , 2015. Likewise, a strong support was found, here and in previous studies, for Gyninae, Panchlorinae and Pycnoscelinae.…”
Section: Discussionsupporting
confidence: 77%
“…Later, cockroach systematists identified several morphological synapomorphies supporting the monophyly of Blaberidae (Grandcolas 1996;Klass & Meier 2006; brood sac underneath the female genitalia, sclerite R3v small, first vein of vannus with many basal rami, tracheation very dense and tracheae vesicle-shaped, presence of a muscle connecting sclerite L2 and pouch lve). Monophyly has also repeatedly been found with molecular data as well (Maekawa et al 2003;Inward 2007;Pellens et al 2007;Djernaes et al 2012;Legendre et al 2014Legendre et al , 2015.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Thus, these results strongly support the paraphyly of Blattodea in relation to termites, as suggested in other studies (e.g. Lo et al 2000;Pellens et al 2007;Legendre et al 2008;Cameron et al 2012;Djernaes et al 2012Djernaes et al , 2015. The current phylogenetic tree supports the sister relation of Blattidae and Blattellidae, with the clade Cryptocercidae + Isoptera as a sister group.…”
Section: Interfamilial Relationssupporting
confidence: 74%
“…In addition, recent phylogenetic studies involving various mitochondrial or/and nuclear molecular markers showed that Cryptocercus is a sister group of a primitive termite species, Mastotermes darwiniensis (Lo et al 2000;Legendre et al 2008;Cameron et al 2012;Djernaes et al 2012). Because of these behavioral characteristics and their close relation with termites, wood-eating cockroaches of Cryptocercus have often been used as model species to elucidate the early stages of social evolution in termites (Klass et al 2008;Djernaes et al 2015).…”
Section: Introductionmentioning
confidence: 99%